3D Printing Applications in Agriculture, Food Processing, and Environmental Protection and Monitoring - Crisostomo, Jan Lloyd Buenaventura; Dizon, John Ryan Cortez (Universitas PGRI Semarang, 2021)
This paper presents a mini review of the applications of 3D printing, formally known as additive manufacturing, in the fields of agriculture, food processing, and the environment protection and monitoring. The paper discusses materials used in 3D printing, the different printing technologies employed in the process, as well as its prospects. PLA and ABS thermoplastics find the most application in the field of agriculture as they are affordable filaments available in the market and they are relatively easy to print. The direct extrusion of food helps people with swallowing difficulties increase their food intake as well as customize their diet. As for the environment, applications in water desalination and air quality monitoring are among the use cases of 3D printing presented in this paper.